2010
DOI: 10.1016/j.otohns.2010.06.329
|View full text |Cite
|
Sign up to set email alerts
|

Complications of CO2 Laser Surgery for Laryngeal Cancer

Abstract: OBJECTIVE:Although PET-CT has been shown to have diagnostic and staging value for the head and neck carcinoma, it still has deficiencies to give an optimal level of sensitivity and specificity. High levels of false positivity continue to be the biggest clinical challenge. This study evaluates the impact of major clinicopathologic factors on PET-CT findings in the primary and lymph node metastatic head and neck carcinoma. METHOD: Retrospective chart review of a case series at Ohio State University Comprehensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…We prescribe all patients proton pump inhibitor therapy immediately postoperatively for a minimum of 4 weeks. Vocal cord granuloma recurrence rates of up to 92% are reported despite careful microsurgical excision . An early second‐look operation enables a thorough examination of the larynx and facilitates simultaneous treatment for local recurrences, division of glottic web, and/or resection of granuloma …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We prescribe all patients proton pump inhibitor therapy immediately postoperatively for a minimum of 4 weeks. Vocal cord granuloma recurrence rates of up to 92% are reported despite careful microsurgical excision . An early second‐look operation enables a thorough examination of the larynx and facilitates simultaneous treatment for local recurrences, division of glottic web, and/or resection of granuloma …”
Section: Discussionmentioning
confidence: 99%
“…Vocal cord granuloma recurrence rates of up to 92% are reported despite careful microsurgical excision. 22 An early second-look operation enables a thorough examination of the larynx and facilitates simultaneous treatment for local recurrences, division of glottic web, and/or resection of granuloma. 10 Postoperative hemorrhage seems to be the most frequent complication and can be minor, major, or catastrophic.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is important to highlight that the complication rate for glottic, supraglottic, and hypopharyngeal tumors, at all stages, that have been operated on by experienced surgeons ranges between 3% and 19%. 3 12 16 17 This hypothesis may be confirmed by comparing tumor size, tumor location, and level of surgeon experience with the occurrence of complications. 3 Moreover, we must emphasize the limitations of our study.…”
Section: Discussionmentioning
confidence: 88%
“…As for associating TLM with neck dissection, some authors suggest ligation of the laryngeal branches of the external carotid artery. 12 Moreover, Ellies and Steiner, in a study that included 1,528 patients treated for TLM, showed 4.7% (72 patients) incidence of post-surgical bleeding. External carotid ligation was required on 7 of such cases.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation